Ion Channel Dysfunction in Astrocytes in Neurodegenerative Diseases - Wang, Sijian; Wang, Biyao; Shang, Dehao; Zhang, Kaige; Yan, Xu; Zhang, Xinwen (Frontiers in Physiology, 2022)
Astrocytes play an important role in the central nervous system (CNS). Ion channels in these cells not only function in ion transport, and maintain water/ion metabolism homeostasis, but also participate in physiological processes of neurons and glial cells by regulating signaling pathways. Increasing evidence indicates the ion channel proteins of astrocytes, such as aquaporins (AQPs), transient receptor potential (TRP) channels, ATP-sensitive potassium (K-ATP) channels, and P2X7 receptors (P2X7R), are strongly associated with oxidative stress, neuroinflammation and characteristic proteins in neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD) and amyotrophic lateral sclerosis (ALS). Since ion channel protein dysfunction is a significant pathological feature of astrocytes in neurodegenerative diseases, we discuss these critical proteins and their signaling pathways in order to understand the underlying molecular mechanisms, which may yield new therapeutic targets for neurodegenerative disorders.